Calculation and comparison of heat transfer coefficient & heat flux by varying the parameters for SCWR through CFD simulations; Научная инициатива иностранных студентов и аспирантов; Т. 2 - Fidel Castro Parimala Rangan (Science as a vocation and career, 2021)
Заглавие с титульного экрана